Outcome after systemic thrombolysis is predicted by age and stroke severity: an open label experience with recombinant tissue plasminogen activator and tirofiban - Rudiger J. Seitz; Judith Sukiennik; Mario Siebler (MDPI AG, 2012)
Stroke patients can recover upon intravenous thrombolysis but remain impaired in lacking recanalization. We sought to investigate the clinical effect of systemic thrombolysis with an intravenous bolus of 20 mg recombinant tissue plasminogen activator (rtPA) and an infusion of body-weight adjusted tirofiban for 48 hours in acute stroke. This prospective, open label study, included 192 patients (68±13 years, 50% males) treated between 1 January 2005 and 31 December 2007. The neurological deficit was assessed with the National Institutes of Health stroke scale (NIHSS). Follow-up was performed using a telephone interview of modified Rankin Scale (mRS) and Barthel index. The site of cerebral artery occlusion was determined by computed tomography or magnetic resonance angiography. Data were analyzed by descriptive statistics and multiple regression analyses. Eighty-one percent of the patients had an infarct in the middle cerebral artery (MCA) territory and were severely affected with a median NIHSS of 10. During treatment on the Stroke Unit the patients improved (P<0.0001) except for patients who deceased due to malignant infarction (n=10) or cerebral haemorrhage (n=6); 18 percent deceased within 100 days which was predicted by older age (76 + 10 years, P<0.05) and more severe affection on admission (P<0.0001). Also, these patients more frequently had atrial fibrillation (P<0.03) than the surviving patients. The surviving patients had more frequently distal MCA occlusions and improved further (P<0.0001). At follow-up 48% of the patients had a mRS of 0 and 1. Similarly to intravenous thrombolysis with body-weight adjusted rtPA, poor prognosis was predicted by higher age, more severe neurological deficit at stroke admission, and a proximal MCA occlusion. Half of the surviving patients improved to no or minimal impairment.